2019
DOI: 10.1186/s40663-019-0187-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing near-natural planting patterns for plantation forests in China

Abstract: Background: China has a long tradition of managing planted forests. Different species of Populus, Eucalyptus, Larix, Cunninghamia and Pinus are planted to satisfy the local demand for wood products and provide ecological services at the same time. Evidence of the greater resilience of natural forests provides the motivation to develop asymmetric planting patterns, which is the focus of this study. We present a new method for designing plantation patterns that follow those observed in natural ecosystems and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
0
16
0
2
Order By: Relevance
“…However, plantations, especially new artificial forests, did not show the same result. The symmetrical and orderly arrangement of individuals in plantations makes the spatial pattern different from the natural forests [19]. However, we only know the quantity advantage of random trees, but its importance in natural forests is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, plantations, especially new artificial forests, did not show the same result. The symmetrical and orderly arrangement of individuals in plantations makes the spatial pattern different from the natural forests [19]. However, we only know the quantity advantage of random trees, but its importance in natural forests is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Each W i value matches a different pattern of neighbours 40 . For convenience, we named the small pattern formed by the reference tree and its nearest four neighbours the structural unit 50 . Each structural unit is composed of five trees: one reference tree and four nearest neighbours.…”
Section: Uniform Angle Index (W)mentioning
confidence: 99%
“…However, restoring Aleppo pine forest resilience and overall functioning could be better achieved by treatments that seek to promote structural and functional complexity within the stands, mimicking natural and healthy forests (Boyden et al 2005;Churchill et al 2013), while maintaining similar levels of residual tree growth and productivity. Similarly, it has been suggested that near-natural arrangements of planted trees could increase the resilience of forest stands as compared with regularly spaced stands (Zhang et al 2019). Furthermore, an aggregated pattern of pine thinning creates a mosaic of tree patches and gaps where understory vegetation can thrive, particularly if resprouter species are present in the area, contributing to increase the structural complexity and heterogeneity of the ecosystem, thus providing niches for biodiversity and promoting higher functional diversity of plants.…”
Section: Conclusion and Management Implicationsmentioning
confidence: 99%